Insights into Financial Strategy Management: A Qualitative Study of Performance, Investment Decisions, and Strategic Approaches with Literature Review - Gazali, Agus Umar; Salle, Ilham Z; Arifani, Arifani; Hasmawati, Hasmawati; Winarti, Winarti (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
Financial strategy management is critical to organizational success, encompassing performance evaluation, investment decision-making, and strategic approaches. This study aims to provide insights into these dimensions by conducting a qualitative literature review. The research methodology comprehensively examined existing scholarly works on financial strategy management, including empirical studies, theoretical frameworks, and practical insights. Performance evaluation emerged as a multifaceted endeavor, requiring a balanced approach that integrates financial and non-financial metrics. Scholars emphasized the importance of robust performance measurement frameworks tailored to organizational objectives and contexts despite data availability and stakeholder alignment challenges. Investment decision-making was explored through the lenses of Modern Portfolio Theory, the Capital Asset Pricing Model, and advancements in behavioral finance. The research highlighted the significance of understanding risk-return trade-offs and cognitive biases influencing investment decisions, particularly in evolving market dynamics and technological disruptions. Strategic approaches adopted by organizations were examined, including Porter's Generic Strategies and recent research on strategic alignment, organizational agility, and integrating environmental, social, and governance (ESG) considerations. The findings underscored the importance of strategic intent aligned with actionable initiatives, organizational resilience, and sustainability. In conclusion, this study contributes to a deeper understanding of financial strategy management dynamics, offering valuable insights for theoretical discourse and managerial practice. The implications extend to longitudinal studies, comparative analyses, interdisciplinary research, and qualitative methodologies, presenting avenues for future research endeavors.